2018
DOI: 10.1097/bpo.0000000000001186
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional MRI Analysis of Femoral Head Remodeling After Reduction in Patients With Developmental Dysplasia of the Hip

Abstract: Level IV-case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…On the one hand, MRI can visualize the cartilage surface. Besides, recent developments in image analysis techniques have enabled 3D morphological analysis based on MRI both from other groups and our own research [30,31]. Further investigations, which are based on an evaluation method that considers cartilage thickness, such as MRI, are necessary to validate the present results.…”
Section: Plos Onementioning
confidence: 73%
“…On the one hand, MRI can visualize the cartilage surface. Besides, recent developments in image analysis techniques have enabled 3D morphological analysis based on MRI both from other groups and our own research [30,31]. Further investigations, which are based on an evaluation method that considers cartilage thickness, such as MRI, are necessary to validate the present results.…”
Section: Plos Onementioning
confidence: 73%
“…In a follow-up study, the same author again used three-dimensional MRI to evaluate 10 of these hips at an average of 18 months postreduction and found that the areas of the femoral head that were aspherical prereduction had largely remodeled and were similar to the contralateral unaffected hip. 14 Sankar et al 9 used arthrogram and fluoroscopy at the time of reduction to measure femoral head sphericity in 37 hips. They found that the femoral head is usually dysplastic and aspherical in DDH; however, there was significant variability in the sphericity of the femoral head in dislocated hips at the time of reduction.…”
Section: Discussionmentioning
confidence: 99%
“…They found that the diameter of the dislocated femoral head was smaller and the head aspherical compared with the unaffected contralateral femoral head. In a follow-up study, the same author again used three-dimensional MRI to evaluate 10 of these hips at an average of 18 months postreduction and found that the areas of the femoral head that were aspherical prereduction had largely remodeled and were similar to the contralateral unaffected hip 14 . Sankar et al 9 used arthrogram and fluoroscopy at the time of reduction to measure femoral head sphericity in 37 hips.…”
Section: Discussionmentioning
confidence: 99%
“…This is also the principle of conservative treatment for DDH in infancy ( 39 ). In immature patients with skeletal development, when the mechanical environment of the femoral head growth plate improves, it can cause deformation of the femoral head shape ( 40 42 ). Therefore, early intervention is necessary when abnormal head-acetabulum relationships are occurred to prevent abnormal growth and development of the epiphysis and growth plates due to long-term abnormal mechanical stress, which can affect the postoperative effect.…”
Section: Discussionmentioning
confidence: 99%